Perencanaan Strategi Digital Pencari Bahan Bakar Desa Sei Beras Sekata Menggunakan Metode Design Thinking - Septiani Sari; AnissaTun Sa’adah; Arif Amrulloh (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
Queues in various service locations such as hospitals, banks, and gas stations (SPBU) often create tedious experiences for the public. Sipermi, an application for selling fuel and kitchen necessities, is designed as a solution to address queuing issues at gas stations. Through the design of User Interface (UI) & User Experience (UX), the application provides detailed information on gas station locations, prices, and promotions, enabling users to place orders without waiting in line. The User Experience Questionnaire (UEQ) results from 10 users indicate an attraction rate of 90%, efficiency of 60%, clarity of 80%, and accuracy of 80%, indicating a high level of satisfaction and comfort in using this application.